Linking Planning and Implementation with the Realization of the Health Operational Assistance Budget in Kolaka and East Kolaka - Rukayah Rukayah; Sunarsih Sunarsih; Erwin Azizi Jayadipraja (Waluya The International Science of Health Journal, 2026)
Introduction: Health issues in Indonesia, particularly in Kolaka and East Kolaka Regencies, still face significant challenges in improving access to quality healthcare services. Community Health Centers, as primary health care facilities, rely heavily on Health Operational Assistance Funds for their operations. However, Health Operational Assistance budget realization shows significant variation between the two regencies, caused by factors such as budget management, human resource capacity, and infrastructure challenges. This study aims to analyze Linking Planning and Implementation with the Realization of the Health Operational Assistance Budget in Kolaka and East Kolaka. Method: This research is quantitative and uses a cross-sectional study design. It was conducted in all community health centers within the jurisdiction of the Kolaka and East Kolaka District Health Offices. The population comprised 72 Health center employees involved in policy-making and budget management, resulting in a sample size of 70. The sample size was calculated using the Lameslow formula. Result: This indicates that planning has a strong relationship with the realization of Health Operational Assistance funds, with Pearson Chi-Square values ​​of 20.822 and 15.892, respectively, and a significance of 0.000. Meanwhile, implementation shows a moderately significant relationship with a Pearson Chi-Square value of 15.892 and a significance of 0.000. Conclusion: Planning has a strong relationship with the realization of the Health Operational Assistance budget in Kolaka and East Kolaka Regencies, while implementation has a moderate relationship. The effectiveness of Health Operational Assistance fund use is most influenced by sound planning and guidance.